A neighbor of Gonoa: "The Man of Bunige" and his game - Musch, Tilman (Journal of Global Archaeology, 2023)
This article presents the rock art site of Bunige in northern Tibesti (Republic of Chad). Bunige is located barely ten kilometers from the rock art site of Gonoa and, except for a short mention in a French article from 1966, does not seem to have been explored in any detail. In addition to engravings of cattle, wild animals, and round devices, there is an almost man-sized depiction of an archer. Such large depictions of humans are very rare in the Tibesti, which makes this ‘Man of Bunige’ in close proximity to the famous ‘Man of Gonoa’ all the more significant. For this reason, the present article describes the rock art site of Bunige in detail. Assuming that the ‘Man of Bunige’ represents a hunter, particular attention will be payed to representations of game and traps at this site. In fact, Bunige, due to its abundance of water, may have attracted wild animals and therefore may have been of particular interest to hunters.